Design of microstrip patch antenna using Fennec Fox optimization with SSRR metamaterial for terahertz applications - Kumari, Sangeeta; Kumar, Arvind; Anbalagan, Ettiyappan; Thoti, Kiran Kumar; Sharma, Manoj (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
This paper presents the design of a microstrip patch antenna based on a Square Split Ring Resonator (SSRR). Wireless technology is switching from 4G to 5G due to the need to overcome limitations, such as low throughput, high latency and path loss. To increase data transfer speeds, the next generation of wireless networks uses 5G terahertz technology. The use of microstrip patch antennas in wireless technologies has increased significantly due to their low cost and simplicity of design as well as the ease of printed circuit board fabrication. However, in some cases their use is limited by low bandwidth, low gain and low throughput. To solve these problems, the Fennec Fox optimization algorithm is used. The algorithm allows you to optimize the length of the microstrip patch antenna resulting in increased gain and reduced return loss. Bakelite is used as a substrate. The width of the patch antenna is set according to the most suitable length selected. To increase the bandwidth and Voltage Standing Wave Ratio (VSWR), a square split ring resonator (SSRR) is used as a metamaterial. An evaluation of the designed microstrip patch antenna model with existing patch antennas was performed. The estimated values of the parameters of the proposed model were the following values: return loss –72.54 dB, resonant frequency 1.11 THz, achieved gain 15.25 dB, VSWR value 1.5646. The estimated values of the developed model exceed those of existing samples. Thus, the developed microstrip patch antenna using Fennec Fox optimization and square split ring resonator metamaterial shows better results in the terahertz range.